Manajemen risiko pembiayaan dan risiko pasar dalam menjaga stabilitas Bank Syariah di era ketidakpastian ekonomi - Qomariyah, Rif'atul (Maliki Interdisciplinary Journal, 2026)
Global economic uncertainty characterized by exchange rate fluctuations and financial market dynamics tend to the stability of Islamic banks, these conditions require the implementation of effective risk management, especially on financing and market risks so that market performance is maintained. This study aims to analyze the role of financing and market risk management in maintaining the stability of Islamic banks in the economic era and identify challenges in its management. The method used is qualitative with literature studies from various relevant sources. The results of the study show that this occurs when it is unable to meet the requirements so that it can reduce the quality of bank assets while market prices appear changes in value such as and which have an impact on the income and value of Islamic bank assets. In addition, the implementation of risks that are not fully adaptive to changes in economic conditions is an obstacle in maintaining stability, therefore it is necessary to strengthen risk management through the process of collecting management monitoring and risk control as well as frequent integration so that Islamic banks remain stable amidst unmentioned economic conditions.